FINANCIAL PERFORMANCE ANALYSIS OF CONSUMER GOODS INDUSTRY COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX (JII) BEFORE AND DURING COVID-19 - Husna Hayati; Heny Rofizar; Asmah Savitri; Angga Syahputra (JURNAL MANAJEMEN DAN BISNIS, 2021)
Corona Virus Disease (Covid-19) that hit Indonesia has had a negative impact on many sectors. The biggest impact is on the decline in economic capacity felt by various business sectors. The economic downturn will also affect the company's financial performance. More specifically, the impact on the company's financial performance is on the company's profitability ratios. This study aims to examine the impact of the Covid-19 pandemic on the financial performance of companies listed on the Jakarta Islamic Index (JII). The research population is 30 companies registered with JII. The sampling technique used is purposive sampling by setting criteria and selecting four companies that meet the criteria set by the author. The overall sample used is the Consumer Goods Industry sector which has remained in JII for 3 consecutive years. Data analysis in this study used the Wilcoxon Signed Rank Test. The results showed that there was a significant difference in Return on Assets before the Covid- 19 pandemic compared to during Covid-19. On the other hand, there is no significant difference in Return on Investment before Covid-19 compared to during Covid-19.